Formation of brown carbon on Fe-bearing clay from volatile phenol under simulated atmospheric conditions. (1st May 2020) - Ling, Jingyi; Sheng, Feng; Wang, Yi; Peng, Anping; Jin, Xin; Gu, Cheng
Abstract: Atmospheric brown carbon (BrC) has recently attracted great concerns due to its potential contribution to climate change. It was reported that dissolved Fe(III) species can act as an efficient oxidant to catalyze the polymerization of volatile phenol substances, subsequently forming atmospheric BrC in aerosols. Since Fe in the atmosphere is commonly associated with clay mineral dusts, the transformation of phenol substances on Fe-bearing clay mineral surface is potentially important for BrC formation. In this study, taking guaiacol as the model phenol substance, its brown carbon formation process was investigated on Fe(III) modified montmorillonite under different relative humidities (RHs). The spectroscopic features and compositions of the produced BrC were systematically characterized. The results demonstrated that the interface FeOH 2+ is the key species to promote the polymerization of guaiacol, and RH plays a significant role to influence the surface acidity of clay and the gas-to-particle adsorption of guaiacol. The BrC was produced with the most abundance and variety under moderate RH (~33%), while higher RH (~100%) accelerated the polymerization rate. Since aerosol moisture content might not largely influence the hydroxylation states of the surface bearing Fe(III) species, it signifies the importance of clay associated Fe(III) to catalyze the BrC formation in varied conditions Our study highlights the importance of clay mineral dust on the formation of BrC, and reveals the brown carbon formation pathways under environmentally relevant conditions. Graphical abstract: Image 1 Highlights: Clay associated Fe(III) promotes BrC formation of guaiacol via polymerization. Interlayer FeOH 2+ is the key reactive species for the polymerization reaction. RH affects the yield and progress but not the pathway of BrC formation. Spectroscopy property and polymer composition of the produced BrC are identified. HPLC-QTOF-MS is potentially effective for studying aerosol BrC.